2006
DOI: 10.1017/s0025315406013415
|View full text |Cite
|
Sign up to set email alerts
|

A temporal and spatial investigation of cyanophage abundance in the Gulf of Aqaba, Red Sea

Abstract: The aim of this study was to determine the abundance of cyanophages over an annual cycle in the Red Sea from the period April 1999 to December 1999 at a range of depths. Cyanophage numbers from 71 water samples were determined by the use of plaque assays using four di¡erent Synechococcus strains. The results indicate that cyanophage are found throughout the water column from surface waters to depths of 150 m, with a discrete maximum in the number of cyanophages in the summer months of July, August and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…The use of Synechococcus strains not generally used for phage isolation may partially explain this. Alternatively, some of the unidentified cyanophages reported previously (37,38,40) may belong to the TIM5-like lineage, but were not sequenced so could not be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Synechococcus strains not generally used for phage isolation may partially explain this. Alternatively, some of the unidentified cyanophages reported previously (37,38,40) may belong to the TIM5-like lineage, but were not sequenced so could not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Strangely, this abundant and widespread phage lineage has not been identified previously even though marine cyanobacteria have been used for two decades to isolate phages (9,30,(37)(38)(39). Indeed, it was previously thought that isolates represent the genetic diversity of cyanophages in nature (3).…”
Section: Discussionmentioning
confidence: 99%
“…3A) is similar to that of other studies in a variety of marine locations. In particular, the abundances of total viruses and cyanophages tend to be greatest in warmer seasons and/or lowest in the winter (Waterbury & Valois 1993, Jiang & Paul 1994, Suttle & Chan 1994, Cochran & Paul 1998, Marston & Sallee 2003, Millard & Mann 2006, Sandaa & Larsen 2006, Wang et al 2011, Parsons et al 2012. Some of these studies also found that cyanophage abundances co-vary with cyanobacterial abundance and temperature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that there is a tight coupling between picocyanobacterial abundance and cyanophage titer, either temporally or spatially (4,5,7,11,33). A monthly temporal survey at the same sampling site in the Gulf of Aqaba showed that the diversity and abundance of cyanomyoviruses were correlated to those of cooccurring Synechococcus populations (6).…”
Section: ) and Clusters Mpp-a And Mpp-b For Cyanopodovirusesmentioning
confidence: 99%
“…Cyanomyoviruses and cyanopodoviruses appear to be much more abundant than cyanosiphoviruses in the ocean (11,25,33,34), and cyanopodoviruses are likely as abundant as cyanomyoviruses (21). The genetic diversity of marine cyanomyoviruses and cyanopodoviruses has been extensively investigated using molecular markers (see reference 35 for a review).…”
mentioning
confidence: 99%